Diagnostics and treatment of superficial mycotic infections - Hasse-Cieślińska, Marta (Przewodnik Lekarza/Guide for GPs, 2006)
This study presents the most common superficial mycotic infections - their epidemiology and clinical signs. We analyzed data from the literature and our own experiences dealing with the treatment of dermatophytosis of the skin, scalp and nails, candidiasis of the skin, nails and mucose membranes, as well as akauliosis. The most often used patterns of management and perspectives of modern antimycotic treatment. Antymicotic treatment, irrespective of localization of mycotic infection, should be preceded by the mycological examination, and that is why basic rules of mycological examination of superficial mycotic infections are explained.